THE INFLUENCE OF PRODUCT INNOVATION ON CUSTOMER LOYALTY IN THE BEVERAGE PRODUCT BUSINESS IN TANJUNGPINANG - Dwi Septi Haryani; Yudi Yulius; Nandan Limakrisna (Yayasan Pusat Cendekiawan Intelektual Nusantara, 2023)
One of the business goals is to be able to retain customers and make customers loyal. One of the things that makes customers loyal is product innovation, therefore product innovation is needed in every company to maintain its customers. his study aims to determine the effect of product innovation on customer loyalty of Seven Beverage Products in Tanjungpinang City. The research method used in this research is descriptive with a quantitative approach. The data analysis technique used is descriptive analysis, data quality test, classical assumption test, simple linear regression test, and hypothesis testing with the help of the SPSS 25 program. The results of this study are based on hypothesis testing, the t-test shows that product innovation has a significant effect on customer loyalty. Namely, Product Innovation (X) produces a t-value of 41,986 with a p-value of 0.000. The test results showed a p-value (0.000) < level of significance (= 5%). Meanwhile, in terms of product innovation, Seven has made quite a good innovation, it can be seen from the score obtained on the results of the questionnaire. Then, customer loyalty Seven has received loyalty from its customers, it can be seen from the good score obtained from the customer loyalty variable questionnaire. The conclusion of this study shows that product innovation in Seven beverage products in the city of Tanjungpinang has a significant effect on customer loyalty, and Seven beverage products have made very good product innovations. Then on customer loyalty, Seven products have also gained loyalty from their customers.